Users’ perception of the OH-EpiCap evaluation tool based on its application to nine national antimicrobial resistance surveillance systems - Moura, Pedro; Collineau, Lucie; Sandberg, Marianne; Tomassone, Laura; De Meneghi, Daniele; Norström, Madelaine; Bennani, Houda; Häsler, Barbara; Colomb-Cotinat, Mélanie; Bourély, Clémence; Filippitzi, Maria-Eleni; Mediouni, Sarah; et al. (Frontiers in Public Health, 2023)
Introduction Antimicrobial resistance (AMR) is a One Health (OH) challenge. To achieve or maintain an effective and efficient AMR surveillance system, it is crucial to evaluate its performance in meeting the proposed objectives, while complying with resource restrictions. The OH-EpiCap tool was created to evaluate the degree of compliance of hazard surveillance activities with essential OH concepts across the following dimensions: organization, operational activities, and impact of the surveillance system. We present feedback on the application of the OH-EpiCap tool from a user’s perspective, based on the use of the tool to evaluate nine national AMR surveillance systems, each with different contexts and objectives. Methods The OH-EpiCap was assessed using the updated CoEvalAMR methodology. This methodology allows the evaluation of the content themes and functional aspects of the tool and captures the user’s subjective experiences via a strengths, weaknesses, opportunities, and threats (SWOT) approach. Results and Discussion The results of the evaluation of the OH-EpiCap are presented and discussed. The OH-EpiCap is an easy-to-use tool, which can facilitate a fast macro-overview of the application of the OH concept to AMR surveillance. When used by specialists in the matter, an evaluation using OH-EpiCap can serve as a basis for the discussion of possible adaptations of AMR surveillance activities or targeting areas that may be further investigated using other evaluation tools.